Partial discharge detection and location technique based on segmented correlation trimmed mean algorithm for power cable / \c Chai Chang Yii. - Chai, Chang Yii author (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are as listed ; to evaluate the performance ofRogowski coil (RC) as a PD sensor in on-line multi-end PD location estimation system for power cable PD detection ; to obtain better accuracy of PD location by using the segmented correlation technique in the PD location algorithm ; to develop a robust PD location algorithm which is able to estimate high accuracyPD location in noisy environments by using trimmed mean data filtering technique.